Hubungan Kecanduan Media Sosial Dengan Kualitas Tidur Mahasiswa Universitas Warmadewa Angkatan 2021 - Ida Ayu Dinda Pradnyaswari Kartha; Ni Luh Putu Eka Kartika Sari; I Made Pariartha (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2025)
Significant advancements have been made in the fields of technology, information, and communication throughout this millennium, particularly in the use of social media. The increased use of social media has led to addiction among adolescents, which affects their sleep quality, especially among university students. This study aims to evaluate the respondents' profiles, sleep quality, level of social media dependency, and the relationship between excessive social media use and sleep quality among students of Warmadewa University from the 2021 cohort. An analytical study with a cross-sectional design was employed. The research was conducted at Warmadewa University over a period of four months. A total of 387 participants were selected using purposive sampling. Data were analyzed using SPSS version 27 with Chi-square tests. The findings showed that the majority of respondents were 21 years old (39.0%), female (58.9%), and predominantly from the Faculty of Engineering and Planning (21.7%). Regarding sleep quality, most respondents had good sleep quality (77.0%). The level of social media addiction was dominated by the mild category (74.7%), followed by severe (15.8%) and moderate (9.6%) categories. The correlation analysis revealed a significant relationship between social media addiction and sleep quality (p < 0.05).